2022
DOI: 10.1080/21645515.2022.2071061
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of a trivalent influenza vaccine and persistence of induced immunity in adults aged ≥60 years in Taizhou City, Zhejiang Province, China, during the 2018–2019 season

Abstract: Yearly administration of influenza vaccine with recommendations can help control seasonal influenza epidemics in adults aged ≥60 years. Here, we describe the results of a prospective study observing the immunogenicity and persistence of induced immunity of a trivalent inactivated split-virion influenza vaccine (TIV) in adults aged ≥60 years during the 2018–2019 season in Taizhou City, Zhejiang Province in China. A total of 422 participants completed the study period. Vaccinated participants (284) received a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…GMTs were highest against the H3 strain and about 2.5 times lower against the B strain, but this was similar for the comparator (3 times lower). Although some studies showed comparable high antibody response to all three vaccine strains [13] , [14] , previous investigators reported lower response to influenza B [15] , [16] , [17] . This finding may depend on the properties of influenza B strain used in different studies.…”
Section: Discussionmentioning
confidence: 92%
“…GMTs were highest against the H3 strain and about 2.5 times lower against the B strain, but this was similar for the comparator (3 times lower). Although some studies showed comparable high antibody response to all three vaccine strains [13] , [14] , previous investigators reported lower response to influenza B [15] , [16] , [17] . This finding may depend on the properties of influenza B strain used in different studies.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, standard liquid bolus vaccine groups typically exhibited at least 20% non-responders to the homologous influenza strains incorporated in the vaccine. Effective seroconversion against administered strains varies widely in a clinical setting, with seroconversion rates among vaccinated adults often varying from 30-70% one month after vaccination [65][66][67] . The ability of PNP hydrogel based multivalent vaccines to induce consistently complete seroconversion is a marked improvement over current commercial vaccine technologies.…”
Section: Discussionmentioning
confidence: 99%
“…While the initial hypothesis projected that receipt of vaccinations, including influenza, COVID-19, and Tdap, as well as durations between vaccinations and SARS-CoV-2 exposures may impact the odds of testing positive, experiencing symptoms, or the duration of COVID-19 symptoms, the multivariate regression models did not reveal such influences. There were no significant differences between participants who had recently received influenza, COVID-19, or Tdap vaccinations and those who had not, nor between those who had received vaccinations greater or less than 6 months prior to SARS-CoV-2 exposures, when antibodies are known to wane [ 66 , 70 , 71 , 74 , 76 , 77 ]. Future trials should investigate whether IPV inoculation may complement other vaccines, such as influenza and COVID-19, and boost antibodies for a longer duration.…”
Section: Discussionmentioning
confidence: 99%
“…In any event, researchers recommend additional COVID-19 vaccinations, to serve as "booster shots," to maintain higher antibody levels [67,68]. In terms of immunity, it takes about 2 weeks to mount antibodies from influenza vaccines, with immunity peaking 2 to 4 weeks later and waning between 3 and 6 months after inoculation [73][74][75][76][77]. While it is not known how long poliovirus antibodies last, studies have shown that individuals can still be completely resistant to wild poliovirus 10 or even 18 years after receiving OPV, and some assert that protective effects could potentially last a lifetime [78][79][80].…”
Section: Independent Variablesmentioning
confidence: 99%